1999
DOI: 10.1103/physrevb.60.5694
|View full text |Cite
|
Sign up to set email alerts
|

Multifractal dimension of chaotic attractors in a driven semiconductor superlattice

Abstract: The multifractal dimension of chaotic attractors has been studied in a weakly coupled superlattice driven by an incommensurate sinusoidal voltage as a function of the driving voltage amplitude. The derived multifractal dimension for the observed bifurcation sequence shows different characteristics for chaotic, quasiperiodic, and frequency-locked attractors. In the chaotic regime, strange attractors are observed. Even in the quasiperiodic regime, attractors with a certain degree of strangeness may exist. From t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…(172)(173)(174)(175) is confirmed by a more ellaborated calculation by Durst et al [186] who evaluate the conductante using a diagra- Andreev et al [189] noted that a negative conductivity makes the two-dimensional electron gas unstable. Due to this instability the systems develops a domain structure with an inhomogeneous current pattern, for which the measured resistance would be zero.…”
Section: Microwave-induced Zero Resistance In Two-dimensional Electromentioning
confidence: 90%
See 1 more Smart Citation
“…(172)(173)(174)(175) is confirmed by a more ellaborated calculation by Durst et al [186] who evaluate the conductante using a diagra- Andreev et al [189] noted that a negative conductivity makes the two-dimensional electron gas unstable. Due to this instability the systems develops a domain structure with an inhomogeneous current pattern, for which the measured resistance would be zero.…”
Section: Microwave-induced Zero Resistance In Two-dimensional Electromentioning
confidence: 90%
“…In this case, the system presents a rich power spectrum, a complex bifurcation diagram and different routes to chaos including quasiperiodicity, frequency locking, etc. [152,153,154,155,174]. First return or Poincaré maps are used to analyze unambiguously the underlying attractors [155].…”
Section: Adiabatic Driving: Routes To Chaosmentioning
confidence: 99%
“…[36] and in Refs. [37,38]). We have checked that noise enhances chaos if its level falls within a narrow range, as indicated in Ref.…”
Section: Resultsmentioning
confidence: 99%
“…To date, it has been found that to describe the self-similarity of Corresponding author: Narek Margaryan, Ph.D., research fields: semiconductor phsics, nanotechnology, carbón films, quantum physics. natural materials is not enough just to use one of the fractal dimensions, and the works of different authors [1][2][3][4][5][6][7] show that the multifractal formalism provides such an opportunity. One of the important physical parameters of the nanostructured films is surface potential, which we can calculate using the results obtained by multifractal analysis.…”
mentioning
confidence: 99%
“…These results allow us to propose a mathematical expression that gives an opportunity to evaluate the surface potential of the film, due to the presence of fractal structure on its surface. The methodology of multifractal parameterization of structures of materials is based on the fundamental principles of self-similarity, stochastic and fractal broken symmetry structures of natural materials [4][5][6]. It uses a set of self-similar measures in Euclidean space, so the characteristics of the material can be described more accurately [7][8][9].…”
mentioning
confidence: 99%